Balaghah sebagai ilmu retorika arab: Analisis konseptual, historis, dan aplikatif - Ulumuddin, Muhammad Ikhyau (Maliki Interdisciplinary Journal, 2026)
Balaghah is a branch of Arabic language that plays a central role in understanding the beauty and depth of expression, particularly in the Qur’an and classical Arabic literature. This discipline encompasses three main areas: the science of ma’ani, which examines the appropriateness of sentences to the situation of the conversation; the science of bayan, which discusses how to convey meaning figuratively and clearly; and the science of badi’, which examines the ornaments of linguistic beauty. This article comprehensively explains the meaning, history, development, scope, and contribution of balaghah to the world of Islamic scholarship. The study was conducted through a search of relevant classical and contemporary sources, with the hope that it can serve as a reference for those interested in studying Arabic and the Qur’an.